Impact of phytohormones on wheat resistance to Hessian fly under heat stress - Maldani, Mohamed; Zhu, Lieceng; Jackson, Janaia; Chen, Ming-Shun; Capers, Destiny; Rania, Nazir; Gore, Cailee; Pankey, Hannah; Walker, Johnae (Frontiers in Agronomy, 2024)
The Hessian fly (HF, Mayetiola destructor) is one of the most destructive pests of wheat and wheat-related cereals. Wheat resistance and/or susceptibility to HF are often affected by the levels of phytohormones in plants. In this study, we tested the impact of phytohormones on Molly wheat resistance to HF biotype GP by externally applying phytohormones, including salicylic acid (SA), jasmonic acid (JA), 12-oxophytodienoic acid (OPDA), and auxin (indole acetic acid, IAA) to wheat seedlings under heat conditions. Our results indicated that the impact of externally applied phytohormones on wheat resistance to HF depends on the timing of phytohormone application and/or HF larval density at HF feeding sites in the plants. The early application of SA, OPDA, and IAA enhanced wheat resistance to HF under heat stress at low larval density, while the delayed application of SA, OPDA, and IAA did not affect wheat resistance to HF at high larval density.